Analisis Butir Soal Ujian Sekolah Mata Pelajaran Ilmu Pengetahuan Alam Siswa Kelas VI SD Negeri Gugus 2 Kecamatan Padang Guci Hulu Kabupaten Kaur Tahun Ajaran 2019/2020 - yuniarti, miri; winarni, endang; muktadir, abdul (UNIB Press, 2024)
This study aims to analyze the proportion of basic science competencies, the proportion of cognitive levels, the quality of grade 4, 5 and 6 items on school exam questions for the 2019/2020 school year. This type of research is a quantitative descriptive study. The subjects in this study were students of grade VI SD Negeri 19, SD Negeri 53 and SD Negeri 59. The object of this research was the lattice of questions, questions, answer keys and answer sheets for the school exams for students of Natural Sciences subjects. The technique of collecting data and instruments in this study is documentation. The data analysis technique uses quantitative analysis techniques by calculating validation, reliability, distinguishing power, and level of difficulty. The results of this study indicate that the analysis of items per level for grade 4 has 10 total items, so if the percentage is 20%, for grade 5 the number of items is 18 items, then if the percentage is 36%, and for class 6 the number of items is 22 items if the percentage is 44%.